Aplikasi Model Sistem Dinamik Untuk Perencanaan Pembangkit Listrik Tenaga Air Dalam Rangka Memenuhi Kebutuhan Supply Dan Demand Energi Listrik Di Kepulauan (Studi Kasus: Pulau Madura) - Addin Aditya; Erma Suryani (Politeknik Harapan Bersama, 2018)
One of the energy problems in Indonesia is uneven electrification ratio. According to PT. PLN (Persero) East Java Distribution, Madura Island has the lowest electrification ratio in East Java, which is 59.02%. At present, Madura gets their electricity supply from Java Island through 2 high voltage sea cable circuit 150.000 volts with 2x100 MW capacity. However, that’s not enough to fulfill the Madura electricity demand. This research aims to develop a dynamic model of the hydroelectric power system in order to increase Madura’s electrification ratio. In this research, we use a dynamic system model to analyze both technical and economical aspect of developing the hydroelectric power system. A dynamic system model approach is a part of the concept which means it articulate the problem as a comprehensive system and relation between each element of it. We hope this research can pull the trigger of energy independence which is correspond with local resource especially in the eastern island of Indonesia.